Decission Tree Technique Dalam Menentukan Penjurusan Siswa Menengah Kejuruan - Ika Purnama Sari; Rika Harman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Many problems are found as the selection of majors that are not in accordance with the abilities, personalities, interests and competencies that can be accounted for in learning. Data mining methodology will be applied to determine the majors in the field of studio that will be taken by students, so students are not wrong in choosing majors that will be taken while studying at the Vocational High School (SMK). C4.5 algorithm is used to determine the majors to be taken by students according to their own backgrounds, interests and abilities. Major selection parameters are color blindness, health test and interview. The test and evaluation results show that the Decision Tree C4.5 Algorithm is accurately applied to the suitability of student majors in Vocational High Schools (SMK)